PENGEMBANGAN SISTEM DATABASE ONLINE MONITORING (OnLimo) KUALITAS AIR - Wahjono, Heru Dwi (Center for Environmental Technology, 2005)
Recent water quality decrease has caused difficult in finding clean water source for people and their daily life. Monitoring on water quality had been carried out many times, from up stream to down stream. ItÃ¢â‚¬â„¢s necessary to do Online Monitoring on ground and underground water quality continuously, so that the effect of water quality decrease could be detected earlier and handle directly. The output of water quality data needs to be processed so that the society and the decision makers could see the information publicly. So, we need a design of structured database of online and real-time water quality data processing. Water quality data management using structured data base system could make water source data retracing easier.Ã‚Â Katakunci : database struktur, online monitoring, real time monitoringÃ‚Â